Emerging pathogens in the central nervous system: a cerebral abscess by Streptococcus porcinus - Martínez Bustamante, Daniel; Pérez Cárdenas, Samuel; Arteaga Treviño, Mauricio; Martínez Ponce de León, Ángel Raymundo (UANL. Facultad de Medicina, 2014)
Brain abscesses can cause an incapacitating neurological deicit in up to 50% of patients, thus the reduction of these sequelae becomes the main goal of its timely and speciic surgical and medical treatment. With technological advances in bacteriological identiication and diagnostic imaging, the clinical suspicion can be conirmed, and the speciic etiological agent can be identiied in a larger number of cases. New pathogens have emerged through this process, such as Streptococcus porcinus, in which the ability to affect the central nervous system has not been documented. A clinical case is presented of a brain abscess in an immunocompetent patient, and its favorable response to surgical drainage t hrough a skull burr h ole and nee dle aspiration with antibiotic therapy (ceftriaxone, metronidazole and vancomycin) is discussed.